2021
DOI: 10.3390/vaccines9050410
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant HPV Vaccination to Prevent Recurrent Cervical Dysplasia after Surgical Treatment: A Meta-Analysis

Abstract: Objective: The aim of this meta-analysis was to discuss evidence supporting the efficacy of adjuvant human papillomavirus (HPV) vaccination in reducing the risk of recurrent cervical intraepithelial neoplasia (CIN) 2 or greater after surgical treatment. Methods: A systematic literature search was performed for studies reporting the impact of HPV vaccination on reducing the risk of recurrence of CIN 2+ after surgical excision. Results were reported as mean differences or pooled odds ratios (OR) with 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…The best available evidence regards the prevention of recurrent CIN after surgical treatment [36][37][38]. A recent meta-analysis [39], including 11 studies and 21,310 patients, demonstrated that providing HPV vaccine as an adjunct to conization for CIN reduces the risk of recurrence. The present meta-analysis added another study (Karimi et al, 2020) [31] with 312 more patients to the previous analysis by Di Donato et al [39], and confirmed that HPV vaccination reduces the risk of CIN recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best available evidence regards the prevention of recurrent CIN after surgical treatment [36][37][38]. A recent meta-analysis [39], including 11 studies and 21,310 patients, demonstrated that providing HPV vaccine as an adjunct to conization for CIN reduces the risk of recurrence. The present meta-analysis added another study (Karimi et al, 2020) [31] with 312 more patients to the previous analysis by Di Donato et al [39], and confirmed that HPV vaccination reduces the risk of CIN recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis [39], including 11 studies and 21,310 patients, demonstrated that providing HPV vaccine as an adjunct to conization for CIN reduces the risk of recurrence. The present meta-analysis added another study (Karimi et al, 2020) [31] with 312 more patients to the previous analysis by Di Donato et al [39], and confirmed that HPV vaccination reduces the risk of CIN recurrence. On the other hand, our systematic research revealed that there are scant data regarding the other HPV-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis evaluated 7 studies with a total of 3375 patients and reported a lower rate of CIN1+ recurrence in vaccinated women (6.3% vs. 10.5%, respectively). In addition, the recurrence of CIN1+ attributed to HPV-16 or HPV-18 was also lower in vaccinated women (1.1% vs. 3.1%, respectively) [ 145 ].…”
Section: Hpv Vaccination In People Living With Hivmentioning
confidence: 99%
“…Oncovirus-specific T cells and epitopes have also been characterized in virus-associated tumors, such as MCPyVassociated Merkel cell carcinoma (152); HPV-associated cervical cancer (153,154) and HNSCC (155)(156)(157)(158); EBVassociated nasopharyngeal carcinoma (159,160) and gastric cancer (161); and HBV-associated hepatocellular carcinomas (139,162). Surgical removal of HPV-positive tumors followed by HPV vaccination has shown promising results to prevent cervical cancer recurrence (163,164) and the use of virus-specific T cells or T cells engineered to recognize virus-derived antigens have shown promising results in preclinical models, case reports and clinical trials in multiple cancers (165)(166)(167), suggesting that recognition of viral antigens by cells of the adaptive immune system is a crucial feature controlling the growth and therapeutic response of virus-associated cancers.…”
Section: Exogenous Viruses As Triggers Of Anti-tumor Immune Responsesmentioning
confidence: 99%